Evaluation of the Growth Performance of Spirulina platensis in Different Concentrations of Kosaric Medium (KM) and Papaya Skin Powder Medium (PSPM) - Jahan, Durin Akhter; Lupa, Saymuna Tarin; N, Nur-A-Raushon; Rahman, Md. Hashibur; Ali, Md. Zulfikar; Bhadra, Anuradha; Mahmud, Yahia (Asian Journal of Biological and Life Sciences)
Aim: The aim of the study was to evaluate the efficacy and cost-effectiveness of Spirulina platensis cultivation using different concentrations of Papaya Skin Powder Medium (PSPM) in comparison to Kosaric Medium (KM). The experiment sought to compare the outcomes of Spirulina cultivation under various concentrations of PSPM, with the objective of determining the feasibility of producing S. platensis at a reasonable cost. Materials and Methods: Each concentration was subjected to its respective treatment i.e., T1 (15% PSPM), T2 (20% PSPM), T3 (25% PSPM) and T4 (KM). Each treatment had three replications. The Papaya skin powder was added 15, 20 and 25% in 600 mL distilled water for each and kept in 1000 ml conical flask. The required amount of KM was produced in a 1000 ml conical flask containing 600 ml of distilled water. Results: The initial weight of S. platensis cells was 0.041 g/l, and they reached their maximum weight of 0.714 g/l in KM before decreasing to 0.498, 0.569, and 0.680 g/l in the 15%, 20%, and 25% PSPM, respectively. In comparison to other PSPM concentrations, the 25% concentration showed a considerably (p<0.01) faster growth rate. The proximate composition of Papaya Skin Powder was examined and it was found to have 21.19% protein, 8.45% lipid, 8.13% ash, 51.229 NFE, and 15.95% moisture. Temperature was measured to be between 24 and 31.8°C, pH was 9.3 to 9.53, Dissolved Oxygen (DO) was 4.27 to 6.58 mg/l, voltage between a pH sensitive glass electrode (MVPH) was 128 to 149, and measurements of Total Dissolved Solid (TDS), electric conductivity, and hectopascal pressure unit (hpa%) were 1012 to 1476. Salinity was measured to be between 0.60 and 4.32. Conclusion: The growth rate of S. platensis cells exhibited a higher multiplication rate in KM as compared to various concentrations of PSPM. The rate of cell multiplication exhibited a significantly higher value (p<0.01) when exposed to a concentration of 25% PSPM in comparison to other concentrations. The 25% PSPM can be considered a financially feasible medium for largescale cultivation.
Keywords: Growth performance; Kosaric Medium (KM); Papaya Skin Powder Medium (PSPM); Spirulina platensis